Kritik Terhadap Ajaran Keselamatan Kristen Progresif Berdasarkan Kisah Para Rasul 4:12 - Halawa, Juliusman (GRAFTA: Journal of Christian Religion Education and Biblical Studies, 2024)
One of the important concepts in Christian theology is salvation, which has been a subject of discussion and interpretation. Using Acts 4:12 as the main point, this article examines progressive Christian teachings on salvation. The statement that "there is salvation in no one but Him" ​​is an important basis for the understanding of salvation in the Christian tradition. This study examines various interpretations of the text, primarily from the perspective of progressive theology that advocates universalism and inclusivity. This article aims to increase our understanding of Christian teaching on salvation in the modern world by combining progressive and traditional theological perspectives.